INTERTEXTUALITY IN JAPANESE READING TEXTS: A TEXT-TO-TEXT STUDY ON LEARNING MATERIALS - Nurhadi, Didik; Roni, Roni; Hartanti, Lina Purwaning; Masrokhah, Yuni; Kato, Jun (LLT Journal: A Journal on Language and Language Teaching, 2025)
This paper aims to grasp the structure and development of Japanese language writings. It examines the element of “Toukatsusei,” the unity of meaning and completeness in the text, which is crucial for language acquisition success. This qualitative descriptive study explores Japanese language reading texts by analyzing characteristics and classification based on their features. Using documentation techniques, data were gathered from 106 Japanese-language instruction readings at the State University of Surabaya, Indonesia, and then compiled into data tables. The structure and meaning of texts in situational and cultural settings were investigated using the referential matching and distribution approach. The findings reveal that emphasis on the subject and coherence in description books depended much on repetition. A coherent story was developed by repeating words, phrases, clauses, and sentences—both whole and in part. Furthermore, it was beneficial to create a unity of meaning and a coherent text structure using conjunctions “tenkagata” and “gyakusetsugata.” This emphasizes how well the Japanese language expresses links between concepts and strengthens the text’s descriptive framework.